Structural Control of Gold Deposits in the Northern Margin of the North China Platform - Wang, Jiapeng; Yin, Jianzhao; Chao, Yuhong; Yin, Yuhan; Xiang, Shoupu; Shi, Hongyun (European Journal of Applied Sciences, 2022)
The North China Platform is one of the oldest continental crusts in China. The northern margin of the North China platform is one of the top gold mining concentration areas in China. Studying its ore-controlling factors is of great practical significance for finding similar gold deposits in areas with similar geological backgrounds. The authors of this paper have concluded that the gold deposits in the northern margin of the North China platform are mainly controlled by various faults. In the long geological history, these fault structures have undergone many stages of activation and transformation almost without exception. Generally, it has experienced the following three stages of development and evolution: 1. Beginning in the early stage of ductile deformation at the end of the Archean period, it is characterized by mylonite. The rock is transformed from the original high amphibolite facies-granulite facies into greenschist facies through ductile shearing. The typical mineral combination is sericite + chlorite + quartz ± feldspar. 2. The brittle-ductile deformation stage occurred in the Hercynian period, that is, the middle activation stage. Due to the different lithology of activation in different sections, the uneven strain of the mining area is caused. Some of the rocks are of continuous inhomogeneous strain, while others are of discontinuous inhomogeneous strain. As a result, hardening in plastic deformation occurs in some areas, and two different types of ore would appear in some mine. 3. The late transformation stage occurred in the early Yanshanian orogeny. It is mainly manifested in the strong fragmentation and transformation of the existing ore bodies, resulting in the dislocation of the ore bodies and complicating their occurrence. This late transformation stage has created favorable conditions for the later oxidative secondary enrichment of ore.